2015
DOI: 10.1017/s1368980015002943
|View full text |Cite
|
Sign up to set email alerts
|

The association between soya consumption and serum thyroid-stimulating hormone concentrations in the Adventist Health Study-2

Abstract: Objective Consumers may choose soya foods as healthful alternatives to animal products, but concern has arisen that eating large amounts of soya may adversely affect thyroid function. The present study aimed to examine the association between soya food consumption and serum thyroid-stimulating hormone (TSH) concentrations in North American churchgoers belonging to the Seventh-day Adventist denomination that encourages vegetarianism. Design Participants completed six repeated 24 h dietary recalls within a 6-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
1
11
0
1
Order By: Relevance
“…These findings are in accord with an observational cohort showing high consumption of soya was associated with elevated TSH concentration in women. (28) Soy consumption is associated with thyroid disorders such as hypothyroidism, goiter, and autoimmune thyroid disease. (29) In vitro studies have demonstrated that isoflavones inhibit thyroid peroxidase (TPO) and inhibit iodide.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in accord with an observational cohort showing high consumption of soya was associated with elevated TSH concentration in women. (28) Soy consumption is associated with thyroid disorders such as hypothyroidism, goiter, and autoimmune thyroid disease. (29) In vitro studies have demonstrated that isoflavones inhibit thyroid peroxidase (TPO) and inhibit iodide.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro inhibition of thyroperoxidase activity was not followed by disturbance of thyroid gland metabolism in people consuming foods rich in flavonoids, even with the intake of isolated genistein in post-menopausal women [ 408 ]. In a cross-sectional epidemiological study on North American churchgoers belonging to the Seventh-Day Adventist church, a significant positive association between soy intake and thyroid-stimulating hormone (TSH) in women but not in men was found [ 409 ]. Though, the relatively low intake of iodine in the cohort can partially explain the thyroid susceptibility to soy.…”
Section: Health Effectsmentioning
confidence: 99%
“…An observational study conducted on 548 women and 295 men belonging to the Seventh‐day Adventist church, which encourages vegetarianism, found a positive association between soy food consumption and serum TSH levels only in women …”
Section: Human Studies Describing Effects Of Phytochemicals In Relatimentioning
confidence: 99%
“…Results in human studies have reported no significant or conflicting evidence regarding the effects of soy isoflavones or other phytocompounds on adult thyroid function . It should be noted that the types of outcomes and sensitivity to phytoestrogens depend on the levels of exposure (amount and duration) and the patients’ estrogenic status .…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%